Case Report: Second Report of Joubert Syndrome Caused by Biallelic Variants in IFT74 - Zhongling, Ke; Guoming, Li; Yanhui, Chen; Xiaoru, Chen (Frontiers in Genetics, 2021)
Joubert syndrome (JBTS) is a rare ciliopathy characterized by developmental delay, hypotonia, and distinctive cerebellar and brain stem malformation called the molar tooth sign (MTS). We reported a 15-month-old female with dysmorphic features (flat nasal bridge, almond-shaped eye, and a minor midline notch in the upper lips), hypotonia, polydactyly, development delay, and MTS. Whole exome sequencing revealed biallelic heterozygous mutations c.535C>G(p.Q179E/c.853G>T) (p.E285*) in IFT74, which were inherited from the parents. So far, only one article reported JBTS associated with IFT74 gene mutation, and this is the second report of the fifth patient with JBTS due to variants in IFT74. All five patients had developmental delay, postaxial polydactyly, subtle cleft of the upper lip, hypotonia, and MTS, but notably without renal and retinal anomalies or significant obesity, and they shared the same mutation c.535C>G(p.Q179E) in IFT74, and c.853G>T(p.E285*) that we found was a new mutation in IFT74 that related with Joubert syndrome. Those findings highlight the need for the inclusion of IFT74 in gene panels for JBST testing.